The therapeutic potential of the insect metalloproteinase inhibitor against infections caused by Pseudomonas aeruginosa. (8th November 2018) - Eisenhardt, Michaela; Schlupp, Peggy; Höfer, Frank; Schmidts, Thomas; Hoffmann, Daniel; Czermak, Peter; Pöppel, Anne-Kathrin; Vilcinskas, Andreas; Runkel, Frank
Abstract: Objectives: The objective of this study was to investigate the therapeutic potential of the insect metalloproteinase inhibitor (IMPI) from Galleria mellonella, the only known specific inhibitor of M4 metalloproteinases. Methods: The fusion protein IMPI-GST (glutathione-S-transferase) was produced by fermentation in Escherichia coli and was tested for its ability to inhibit the proteolytic activity of the M4 metalloproteinases thermolysin and Pseudomonas elastase (PE), the latter a key virulence factor of the wound-associated and antibiotic-resistant pathogen Pseudomonas aeruginosa . We also tested the ability of IMPI to inhibit the secretome (Sec) of a P. aeruginosa strain obtained from a wound. Key findings: We found that IMPI-GST inhibited thermolysin and PE in vitro and increased the viability of human keratinocytes exposed to Sec by inhibiting detachment caused by changes in cytoskeletal morphology. IMPI-GST also improved the cell migration rate in an in vitro wound assay and reduced the severity of necrosis caused by Sec in an ex vivo porcine wound model. Conclusions: The inhibition of virulence factors is a novel therapeutic approach against antibiotic resistant bacteria. Our results indicate that IMPI is a promising drug candidate for the treatment of P. aeruginosa infections.